In vitro elution of analgesic medications from an absorbable gelatin sponge - Baker, Steven Gerald (Kansas State University, 2011)
Objective: To compare the in vitro elution characteristics of six common analgesic medications from a commercially available absorbable gelatin sponge. Study Design: Experimental study. Methods: Gelatin sponges were loaded with various analgesic medications, including two opioids, preservative-free morphine and fentanyl, two local anesthestics, bupivacaine and lidocaine, and two α2-adrenergic agonists, dexmedetomidine and xylazine. The loaded sponges were placed in dishes containing phosphate-buffered saline (PBS) and maintained at 37° C with constant agitation. Concentrations of each drug were determined at various time points up to 24 hours post-inoculation using high-pressure liquid chromatography. Two phases were conducted, utilizing undried loaded sponges (phase one) and dried loaded sponges (phase two). Results: In both phases, all analgesic medications eluted from the gelatin sponge and equilibrated rapidly with the PBS, achieving maximal concentration within 30 minutes. In phase two, the rapid nature of the release was captured by increasing sampling within the initial 30 minutes. Results were consistent for each medication with minimal variation. Steady state concentrations were significantly higher in phase two with four out of six medications. Conclusions: Analgesic medication elution from an absorbable gelatin sponge was rapid and consistent. Drying the loaded sponge prior to use will likely substantially increase the amount of medication eluted but not prolong release. Clinical Relevance: The rapid release of analgesic medications from the gelatin sponge makes a prolonged analgesic effect unlikely without further modification. Toxicity may be a concern. Further study is required to investigate efficacy in vivo, safe dosing regimens and prolongation of duration of action.
Keywords: drug elution; regional analgesia; Veterinary Medicine (0778)